Prevention of the development of problem behavior: A laboratory model. Issue 1 (4th December 2017) - Fahmie, Tara A.; Macaskill, Anne C.; Kazemi, Ellie; Elmer, Uilani C.
Abstract : Few studies have isolated the preventive efficacy of common behavioral strategies like noncontingent reinforcement (NCR) and differential reinforcement of alternative behavior (DRA). The purpose of the current study was to develop and evaluate a laboratory model of these two problem behavior prevention strategies. Undergraduate students participated in a computer simulation, in which clicks to a designated area of the computer screen were analogous to the emergence of problem behavior. The responding of participants in a control group, who experienced a percentile schedule used to mimic the shaping of problem behavior, was compared to that of participants in two experimental groups, each with a history of either DRA or NCR. Between‐subjects group comparisons showed that both intervention strategies were equally effective in the prevention of our analog to problem behavior when compared to the control group. The strengths and limitations of a laboratory model for prevention are discussed in light of recent applied work in this area.